2017
DOI: 10.1002/2016ms000729
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and predictability of secondary eyewall formation in sheared tropical cyclones

Abstract: This study examines the predictability and dynamics of tropical cyclone (TC) secondary eyewall formation (SEF), eyewall replacement cycles (ERC), and intensity changes under moderate environmental shear through convection‐permitting ensemble simulations. Even with the same environmental shear, the TC intensity changes during formation, rapid intensification, and SEF/ERC can be extremely sensitive to small, unobservable, random initial condition uncertainties, or computer's truncation error due to the chaotic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 54 publications
7
44
0
Order By: Relevance
“…Qiu and Tan (2013) observed a similar inflow pattern in a numerical simulation, suggesting that this operates in conjunction with axisymmetric boundary layer mechanisms to trigger SEF by enhancing inflow on the opposite side of the TC. This pathway to SEF has been observed in other numerical simulations Zhang et al, 2017).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Qiu and Tan (2013) observed a similar inflow pattern in a numerical simulation, suggesting that this operates in conjunction with axisymmetric boundary layer mechanisms to trigger SEF by enhancing inflow on the opposite side of the TC. This pathway to SEF has been observed in other numerical simulations Zhang et al, 2017).…”
Section: Introductionsupporting
confidence: 85%
“…It is well established that the SE forms from convection in preexisting spiral rainbands (e.g., Hawkins & Helveston, ). Numerical simulations suggest that SEF is initiated by projection of rainband diabatic heating onto the azimuthal mean (Rozoff et al, ), vorticity accumulation in the outer rainbands (Judt & Chen, ), or boundary layer feedbacks in response to rainband heating and vorticity anomalies (Huang et al, ; Kepert, ; Zhang et al, ). Case studies of SEF events in hurricanes Rita (2005) (Bell et al, ; Didlake & Houze, , ; Houze et al, ) and Earl (2010) (Didlake et al, ) used high‐resolution Doppler radar observations to demonstrate that, in both of these cases, an SE developed from the axisymmetrization of a preexisting SBC.…”
Section: Introductionmentioning
confidence: 99%
“…While the impact of microphysics on SEF is evident from these studies, the possible triggering mechanism of SEF by microphysical processes has yet to be addressed. Zhang et al () analyzed composites of five ensemble members with similar SEF characteristics from an ensemble of WRF‐ARW simulations along with diagnoses from a boundary layer model. Their analyses showed that while boundary layer processes are important in determining the characteristics of SEF, the SEF shown in the composites was not initiated in the boundary layer, but rather originated in the upper levels.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms for SEF have been proposed and frequently discussed, including 1) vortex Rossby wave radiation and the associated wave-mean flow interaction near the critical radius (Montgomery and Kallenbach 1997;Qiu et al 2010;Abarca and Corbosiero 2011;Menelaou et al 2012); 2) axisymmetrization leading to vorticity ring formation outside of the primary eyewall (Kuo et al 2004(Kuo et al , 2008; 3) beta-skirt axisymmetrization in a region with sufficiently long filamentation time and moist convective potential, together with a follow-up wind-induced surface heat exchange (WISHE) process (Terwey and Montgomery 2008;Qiu et al 2010); 4) unbalanced dynamics associated with the TC boundary layer (BL) (Huang et al 2012;Abarca and Montgomery 2013;Wang et al 2013); 5) axisymmetrization and balanced response to latent heating from the outer rainbands in a region of enhanced inertial stability outside the primary eyewall (Fang and Zhang 2012;Rozoff et al 2012;Sun et al 2013;Zhang et al 2017); and 6) positive feedback among local enhancement of the radial vorticity gradient, BL frictional updraft, and convection (Kepert 2013;Kepert and Nolan 2014;Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 99%